INFLUENCE OF PROCESSING PARAMETERS ON RHEOLOGICAL BEHAVIOR OF BENTONITE-BASED PICKERING EMULSION - TOUZOUIRT, saida; KESSAL, Fetta; BELAIDI, Chanez; BOULHALFA, Dihia (Journal of Drug Delivery and Therapeutics, 2018)
The aim of this work is to study the impact of processing parameters on the rheological properties of Pickering emulsions containing bentonite particles, CTAB, NaCl and soybean oil. Emulsification experiments were performed using mixing and homogenization at different speeds for 10 minutes. The effects of stirring speed and homogenization were investigated to determine the best conditions for producing a suitable Pickering emulsion for the intended application. In order to assess the influence of processing parameters on the Pickering emulsion rheological behavior average droplet size was measured and rheological tests were performed on all the emulsions samples. The rheological behavior of these emulsions is modeled by Casson's law. Results show that the stirring speed first decreases the average size of the droplets, and then an effect on the initial viscosity is observed. Increasing the stirring speed increases the values of the initial viscosity in contrast to the infinite viscosity which is influenced by the homogenization speed. On the other hand, these processing parameters significantly affect the values of the yield strength.Keywords: stirring speed, speed homogenization, rheological properties, Pickering emulsion.